The Sports-Related Injuries and Illnesses in Paralympic Sport Study (SRIIPSS): a study protocol for a prospective longitudinal study - Fagher, K.; Jacobsson, J.; Timpka, T.; Dahlström, Ö.; Lexell, J. (BMC Sports Science, Medicine and Rehabilitation, 2016)
Paralympic sport provides sporting opportunities for athletes with a disability, with the Paralympic Games as the main event. Participation in sport is, however, associated with a significant risk for sustaining injuries and illnesses. Our knowledge of sports-related injuries and illnesses in Paralympic sport is very limited and there are no large-scale epidemiological cohort studies. The purpose here is to present a protocol for a prospective longitudinal study: The Sports-Related Injuries and Illnesses in Paralympic Sport Study (SRIIPSS). Methods/design: An argument-based method for investigation of design problems was used to structure the study protocol. The primary requirement of the protocol is to allow prospective studies over time and include exposure to both training and competition. To reflect the complexity of Paralympic sport with athletes` pre-existing impairments, use of assistive equipment, pain and other and medical issues, it is required that the data collection system is specifically adapted to Paralympic sport. To allow the collection of data, at the same time as there is limited access to coaches and medical personnel, it is advantageous that data can be collected online directly from the athletes. Based on this a self-report athlete monitoring system will be developed, where the athletes can enter data weekly via their mobile phones or lap-tops. Data will be collected from around 100 Swedish Paralympic athletes for approximately 1 year, which will allow us to i) prospectively estimate the annual incidence of sports-related injuries and illnesses and ii) explore risk factors and mechanisms for sustaining sports-related injuries and illnesses based on athlete exposure and training loads. Discussion: For effective implementation of injury and illness prevention measures, comprehensive epidemiological knowledge is required. This study will be the first prospective longitudinal self-report study of sports-related injuries and illnesses in Paralympic sport over a longer period of time. The results will eventually contribute to the development of evidence-based preventive measures specifically adapted to Paralympic sport in order to provide safe and healthy sport participation. Thereby, the project will be of relevance for Paralympic athletes at all levels and to the Paralympic Movement.